Factors that influence consumption behaviour of consumers on fruits and vegetables in Klang Valley - Ng, Yin Choo (2018)
Fruits and Vegetables are the significant elements of a healthy diet which can maintain body health and reduce the risk of getting disease. However, most of the Malaysian are still insufficient on consumption fruits and vegetables. The overall objective of this study is to investigate the factors that influence on consumption behaviour of fruits and vegetables among consumers in Klang valley. Systematic random sampling is applied to select 400 respondents in Klang Valley during the survey. The data after collected from survey by answering questionnaire will be analyse with using descriptive analysis, chi-square analysis and factor analysis. According to the results of descriptive analysis, majority of the respondents think that fruits and vegetables are the mainly heathy diet but most of them still consume insufficient fruits and vegetables every day. This is because of the result founded that most of the respondents are consume fruits in between 3 to 4 times in a week while vegetables is more than 7 times in a week. Most of the respondents are not purchase fruits and vegetables every day but is purchase the fruits and vegetables in between 3 to 4 days once with spend only RM100 or less every month for each respectively. Based on the result of chi-square, various demographic factors are significant influence the consumption behaviour of consumers on fruits and vegetables. For the result of factor analysis, there are 5 factors were generated and significant influence the consumption behaviour of consumers on intake fruits and vegetables which are price, attitude, availability, quality and subjective norm. From the result of this study, it allow people to understand the consumption behaviour of Malaysian on consuming fruits and vegetables in order to overcome the problem of consume insufficient on fruits and vegetables. Thus, government, marketer and producer should promoting the factors founded in this study to encourage consumers increase the consumption rate on fruits and vegetables.